2001
DOI: 10.1007/s004210100494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cosmonaut vestibular training on vestibular function prior to spaceflight

Abstract: The purpose of this study was to quantify the effects of repetitive Coriolis and cross-coupled stimulations, similar to the vestibular training the cosmonauts are exposed to prior to their spaceflight. on vestibular function in control subjects on Earth. Ten volunteers were passively rotated in yaw on a rotating chair while executing standardized pitch head-and-trunk movements. The chair stopped to change direction after 12 head-and-trunk movements were made. The runs were grouped in sessions of ten,which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 10 publications
3
26
0
Order By: Relevance
“…This is the Wrst time a reduced sensitivity to MS has been highlighted in people engaging in this type of sporting activity. This result is consistent with the increase in resistance to MS observed after vestibular habituation induced either by cosmonaut vestibular training (Clement et al 2001) or by a month spent at sea (Shupak et al 1990). Even if the VOR tends to decrease through a habituation phenomenon, the skaters use vestibular information more eYciently for postural control.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This is the Wrst time a reduced sensitivity to MS has been highlighted in people engaging in this type of sporting activity. This result is consistent with the increase in resistance to MS observed after vestibular habituation induced either by cosmonaut vestibular training (Clement et al 2001) or by a month spent at sea (Shupak et al 1990). Even if the VOR tends to decrease through a habituation phenomenon, the skaters use vestibular information more eYciently for postural control.…”
supporting
confidence: 90%
“…Thus, after a month of regular navigation, candidates for future maritime service become less sensitive to seasickness and show VOR habituation (Shupak et al 1990). Likewise, repeated stimulation of the vestibular system as part of cosmonaut vestibular training induced both a reduction in gain and TC and a parallel decrease in MS (Clement et al 2001). Repetitive vestibular stimulation can therefore cause changes in VOR and at the same time a reduction in sensitivity to MS.…”
Section: Introductionmentioning
confidence: 98%
“…The stimulus alternately brings the vertical and horizontal canals into and out of the plane of rotation, causing subjects to feel tumbling or pitching, disorientation, and nausea, which can finally result in vomiting. The number of head movements that subjects make before overwhelming nausea has been widely used as an operational definition of motion sickness susceptibility (Lackner and Graybiel 1994;Clément et al 2001;Young et al 2001;Dai et al 2003). A motion sickness score can also be calculated to characterize the level of motion sickness (Miller and Graybiel 1969;Hecht et al 2001;Young et al 2001).…”
mentioning
confidence: 99%
“…This results in non-compensatory nystagmus, inappropriately perceived self-motion, and in some cases motion sickness. Results showed that subjects are able to develop and retain adaptation to inappropriate eye reflexes and perceived sensations of self-motion resulting from head turns during centrifugation (Lyne 2000;Cle´-ment et al 2001b;Young et al 2001). The ability to simultaneously retain two sensory programs, in this case for rotating and non-rotating environments, is referred to as dual adaptation.…”
Section: Current Projectsmentioning
confidence: 94%